Analisis Morfologi Granula Pati dan Kristal Pada Beberapa Jenis Talas - Ema Susiana; Tesri Maideliza; - Mansyurdin (Jurnal Biologi Universitas Andalas, 2013)
The study of comparative characters of starch grain and crystal morphologically had been done among five species of taro from January until April 2013 in Plant Structure and Development Laboratory, Department of Biology, Faculty of Mathematics and Natural Science, Andalas University. The corm of taro species were analyzed the character of shape and size by using fresh preparate. The result showed that X. sagittifolium and X. violaceum have circular starch grain, while C. esculenta cv. 1, C. esculenta cv. 2, C. esculenta cv. 3 have ellip starch grain. The shape of calcium oxalate crystals found is a bundle of raphide, individual raphide and druse. The all species of taro have individual raphide. C. esculenta cv. 1 and C. esculenta cv. 3 have raphides and druse crystal. Keywords : taro, starch, crystals, Xanthosoma, Colocasia